Graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and preparation method thereof

The preparation of graphene nanosheet/magnesium aluminum hydrotalcite composite powder by hydrothermal method solves the problem of poor hydrophilicity of graphene nanosheet composite powder, realizes the preparation of graphene nanosheet/magnesium aluminum hydrotalcite composite powder with simplified process, reduced cost and environmental friendliness, and improves its dispersion performance in aqueous media.

CN120793916APending Publication Date: 2025-10-17WUHAN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511094570.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-06
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

In the existing technology, graphene nanosheet composite powders have poor hydrophilicity, complex processes and high costs, and pose an environmental pollution risk.

Method used

A one-step hydrothermal method was used to prepare graphene nanosheet/magnesium aluminum hydrotalcite composite powder. By combining graphene nanosheets with magnesium aluminum hydrotalcite rich in hydrophilic functional groups, the uniform coating of graphene and magnesium aluminum hydrotalcite was achieved in a closed reactor using a hydrothermal reaction, avoiding the use of toxic solvents and expensive equipment.

Benefits of technology

It significantly improves the hydrophilicity of graphene nanosheet composite powder, simplifies the process, reduces production costs, and is easy to industrialize. The prepared powder is easy to disperse in aqueous media, avoiding agglomeration problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120793916A_ABST
    Figure CN120793916A_ABST
Patent Text Reader

Abstract

The invention relates to graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof. According to the technical scheme, the method comprises the following steps: performing ultrasonic treatment on a graphene nanosheet suspension to obtain a treated suspension; adding a magnesium source and an aluminum source into the treated suspension according to the molar ratio of the magnesium source to the aluminum source to the graphene nanosheets of 1: (0.5-0.7): (0.67-1.67), and stirring to obtain a mixed solution; adjusting the pH value of the mixed solution with a sodium hydroxide solution to obtain hydroxide sol; adding carbonate into the hydroxide sol according to the molar ratio of the magnesium source to the carbonate of 1: (0.067-0.167), and stirring to obtain precursor sol; performing a hydrothermal reaction on the precursor sol to generate a precipitate; and carrying out suction filtration, washing to be neutral, and freeze-drying to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder. The preparation method has the characteristics of simple process, low cost and environmental friendliness, and the prepared graphene nanosheet / magnesium-aluminum hydrotalcite composite powder has excellent hydrophilicity.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of graphene nanosheet composite powder, and particularly relates to a graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof. BACKGROUND

[0002] Graphene nanosheets have been widely used in the preparation of reinforced composite powder materials due to their excellent mechanical properties, high thermal conductivity and large specific surface area. However, the intrinsic hydrophobicity of graphene nanosheets leads to a decrease in the hydrophilicity of graphene nanosheet composite powder prepared therefrom, which limits the application effect. Therefore, the technical personnel in the field still pay great attention to this problem. The patent technology of "Method for preparing sea urchin type microstructure manganese dioxide composite graphene nanosheet powder and application thereof" (CN108585875B) uses a one-step hydrothermal method to prepare manganese dioxide composite graphene nanosheet powder. Although manganese dioxide is hydrophilic, the number of exposed hydrophilic sites on its surface is limited, and the composite method with hydrophobic graphene limits the effective use of hydrophilic groups, so the improvement of the overall hydrophilicity of the composite powder is limited, and the core problem of poor hydrophilicity is not effectively solved.

[0003] The patent technology of "Preparation method of graphene nanosheet composite powder and product" (CN115180618B) uses pulsed alternating shear force to prepare graphene nanosheet composite powder. However, the grinding aid powder used in this process is a hydrophobic material, which results in poor hydrophilicity of the prepared composite powder.

[0004] The patent technology of "Silicon carbide / graphene nanosheet composite material and preparation method thereof" (CN109999870B) uses a vacuum calcination method to prepare silicon carbide / graphene nanosheet composite material. The process conditions are harsh (the reaction temperature is as high as 1000-1250℃), the hydrofluoric acid solution used in the process has strong corrosive property, and there are problems of complex process, high cost, and limited improvement of the hydrophilicity of the composite powder.

[0005] The patent technology of "Silicon carbide-graphene composite powder and preparation method thereof" (CN107311177B) uses a pressureless sintering method to prepare silicon carbide-graphene composite powder under argon protection. The introduction of silicon carbide helps to improve the high-temperature strength and oxidation resistance of the material. However, this method also has limited effect on improving the hydrophilicity of the composite powder. At the same time, the process needs to maintain an argon environment and the reaction temperature is above 800℃, which has problems of complex process, high cost, and the like.

[0006] In summary, the main defects of the existing technology are that the hydrophilicity of the prepared graphene nanosheet composite powder is poor, and there are problems of complex process, environmental impact and high production cost. SUMMARY

[0007] The present application aims to overcome the defects of the prior art, and aims to provide a preparation method of graphene nanosheet / magnesium-aluminum hydrotalcite composite powder, which is simple in process, environmentally friendly and low in production cost.

[0008] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is: The graphene nanosheet suspension is ultrasonically treated to obtain a treated suspension; a magnesium source and an aluminum source are added to the treated suspension in a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.5-0.7:0.67-1.67, and first stirring is performed to obtain a mixed solution; then the mixed solution is adjusted to a pH value of 3-11 with a sodium hydroxide solution to obtain a hydroxide sol.

[0009] A carbonate is added to the hydroxide sol in a molar ratio of magnesium source: carbonate of 1:0.067-0.167, and second stirring is performed to obtain a precursor sol.

[0010] The precursor sol is subjected to hydrothermal reaction to generate a precipitate; the precipitate is suction-filtered, washed with water to neutral, and freeze-dried to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder.

[0011] The graphene nanosheet suspension is prepared by liquid-phase shear exfoliation of graphite, and the concentration of the graphene nanosheet suspension is 4-6 g / L.

[0012] The magnesium source is one of magnesium chloride hexahydrate and magnesium nitrate nine hydrate; the magnesium source is analytical pure or industrial pure.

[0013] The aluminum source is one of aluminum nitrate nine hydrate and aluminum chloride six hydrate; the aluminum source is analytical pure or industrial pure.

[0014] The carbonate is one of anhydrous sodium carbonate and sodium bicarbonate; the carbonate is analytical pure or industrial pure.

[0015] The temperature of the hydrothermal reaction is 110-150 DEG C, and the time of the hydrothermal reaction is 4-12 h.

[0016] The first stirring is magnetic stirring, the time of the first stirring is 15-30 min, and the speed of the first stirring is 600-1000 rpm.

[0017] The second stirring is magnetic stirring, the time of the second stirring is 10-20 min, and the speed of the second stirring is 400-600 rpm.

[0018] The time of the freeze-drying is 24-72 h.

[0019] Due to the adoption of the above technical solution, the present invention has the following beneficial effects compared with the prior art: The graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared by the present invention combines graphene nanosheets with magnesium-aluminum hydrotalcite, which is rich in hydrophilic functional groups. This achieves uniform coating of the graphene nanosheets with the magnesium-aluminum hydrotalcite. This structure significantly enhances the hydrophilicity of the composite powder, making it easier to disperse in aqueous media. This effectively overcomes the difficulty in dispersing and the tendency to agglomerate graphene nanosheet composite powders in aqueous systems, which are commonly encountered in the prior art.

[0020] 2. The graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared by the present invention is simultaneously composited with graphene and magnesium-aluminum hydrotalcite in a closed reactor via a one-step hydrothermal method, resulting in a simple process flow. Because the hydrothermal reaction uses water as the solvent, no additional surface modifier is required to achieve interfacial bonding between the two phases. Furthermore, no toxic byproducts are generated during the reaction process, eliminating the need for expensive equipment, complex surface modifiers, or toxic or hazardous organic solvents. The overall process is not only low-cost and environmentally friendly, but also economically beneficial and easily industrializable.

[0021] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared by the present invention is 63.2-68.4°.

[0022] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared by the present invention was mixed with 9 parts by mass of corundum aggregate (particle size of 0.5-0.074 mm, Al2O3 content of 98 wt%), and then 1 part by mass of deionized water was added. The mixture was stirred evenly, cast into a mold, and dried at room temperature and normal pressure for 72 hours. The prepared corundum-based material body was tested to have a compressive strength of 0.22-0.28 MPa.

[0023] Therefore, the present invention has the characteristics of simple process, low cost, environmental friendliness and easy industrialization, and the prepared graphene nanosheet / magnesium-aluminum hydrotalcite composite powder has excellent hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of a graphene nanosheet / magnesium aluminum hydrotalcite composite powder prepared in the present invention; Figure 2 for Figure 1 The water contact angle diagram of graphene nanosheets / magnesium aluminum hydrotalcite composite powder is shown. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments, which does not limit the scope of protection thereof.

[0026] A graphene nanosheet / magnesium aluminum hydrotalcite composite powder and its preparation method. The preparation method described in this specific embodiment is: The graphene nanosheet suspension is ultrasonically treated to obtain a treated suspension; a magnesium source and an aluminum source are added to the treated suspension at a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.5-0.7:0.67-1.67, and the mixture is stirred for the first time to obtain a mixed solution; and the pH value of the mixed solution is adjusted to 3-11 with a sodium hydroxide solution to obtain a hydroxide sol.

[0027] According to the molar ratio of the magnesium source to the carbonate of 1:0.067-0.167, carbonate is added to the hydroxide sol, and stirred for the second time to obtain a precursor sol.

[0028] The precursor sol is subjected to a hydrothermal reaction to generate a precipitate; the precipitate is filtered, washed with water until neutral, and freeze-dried to obtain a graphene nanosheet / magnesium aluminum hydrotalcite composite powder.

[0029] The concentration of the graphene nanosheet suspension is 4-6 g / L.

[0030] The magnesium source is one of magnesium chloride hexahydrate and magnesium nitrate nonahydrate.

[0031] The aluminum source is one of aluminum nitrate nonahydrate and aluminum chloride hexahydrate.

[0032] The carbonate is one of anhydrous sodium carbonate and sodium bicarbonate.

[0033] The temperature of the hydrothermal reaction is 110-150° C., and the time of the hydrothermal reaction is 4-12 hours.

[0034] The first stirring is magnetic stirring, the first stirring time is 15-30 minutes, and the first stirring speed is 600-1000 rpm.

[0035] The second stirring is magnetic stirring, the second stirring time is 10-20 min, and the second stirring speed is 400-600 rpm.

[0036] The freeze-drying time is 24 to 72 hours.

[0037] In this specific implementation mode: The graphene nanosheet suspension is prepared by subjecting graphite to a liquid phase shear exfoliation method.

[0038] The magnesium source is analytically pure or industrially pure.

[0039] The aluminum source is of analytical grade or industrial grade.

[0040] The carbonate is analytically pure or industrially pure.

[0041] The embodiments are not described again.

[0042] Embodiment 1 The graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof are disclosed. The preparation method is as follows: The graphene nanosheet suspension is ultrasonically treated to obtain a treated suspension; a magnesium source and an aluminum source are added to the treated suspension in a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.5:0.67, and first stirring is performed to obtain a mixed solution; and the mixed solution is adjusted to a pH value of 11 with a sodium hydroxide solution to obtain a hydroxide sol.

[0043] A carbonate is added to the hydroxide sol in a molar ratio of magnesium source: carbonate of 1:0.067, and second stirring is performed to obtain a precursor sol.

[0044] The precursor sol is subjected to hydrothermal reaction to generate a precipitate; the precipitate is suction filtered, washed with water to neutral, and freeze-dried to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder.

[0045] The concentration of the graphene nanosheet suspension is 4 g / L.

[0046] The magnesium source is magnesium chloride hexahydrate; and the magnesium chloride hexahydrate is of analytical purity.

[0047] The aluminum source is aluminum nitrate nonahydrate; and the aluminum nitrate nonahydrate is of analytical purity.

[0048] The carbonate is anhydrous sodium carbonate; and the anhydrous sodium carbonate is of analytical purity.

[0049] The temperature of the hydrothermal reaction is 130°C, and the time of the hydrothermal reaction is 8 h.

[0050] The first stirring is magnetic stirring, the time of the first stirring is 15 min, and the speed of the first stirring is 600 rpm.

[0051] The second stirring is magnetic stirring, the time of the second stirring is 10 min, and the speed of the second stirring is 400 rpm.

[0052] The time of the freeze-drying is 24 h.

[0053] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in the embodiment is 64.9°.

[0054] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this example and 9 parts by mass of corundum aggregate (particle size of 0.5-0.074 mm, Al2O3 content of 98 wt%) were mixed, 1 part by mass of deionized water was added, and the mixture was stirred uniformly, cast, dried at room temperature and under normal pressure for 72 h, and then the corundum-based material green body was prepared. The prepared corundum-based material green body was detected to have a compressive strength of 0.28 MPa.

[0055] Example 2 A graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof. The preparation method described in this example is as follows: The graphene nanosheet suspension was ultrasonically treated to obtain a treated suspension; a magnesium source and an aluminum source were added to the treated suspension in a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.55:1.0, and first stirring was performed to obtain a mixed solution; and the mixed solution was adjusted to a pH value of 9 with a sodium hydroxide solution to obtain a hydroxide sol.

[0056] A carbonate was added to the hydroxide sol in a molar ratio of magnesium source: carbonate of 1:0.1, and second stirring was performed to obtain a precursor sol.

[0057] The precursor sol was subjected to hydrothermal reaction to generate a precipitate; the precipitate was suction filtered, washed with water until neutral, and freeze-dried to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder.

[0058] The concentration of the graphene nanosheet suspension is 4.5 g / L.

[0059] The magnesium source is magnesium nitrate nine hydrate; the magnesium nitrate nine hydrate is of industrial purity.

[0060] The aluminum source is aluminum chloride six hydrate; the aluminum chloride six hydrate is of industrial purity.

[0061] The carbonate is sodium bicarbonate; the sodium bicarbonate is of industrial purity.

[0062] The temperature of the hydrothermal reaction is 110°C, and the time of the hydrothermal reaction is 4 h.

[0063] The first stirring is magnetic stirring, the time of the first stirring is 20 min, and the rotating speed of the first stirring is 700 rpm.

[0064] The second stirring is magnetic stirring, the time of the second stirring is 15 min, and the rotating speed of the second stirring is 450 rpm.

[0065] The time of the freeze-drying is 36 h.

[0066] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this example is 68.4°.

[0067] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this example was mixed with 9 parts by mass of corundum aggregate (particle size of 0.5-0.074 mm, Al2O3 content of 98 wt%), 1 part by mass of deionized water was added, and the mixture was uniformly stirred and cast, and then dried at room temperature and normal pressure for 72 h. The corundum-based material green body prepared in this way was detected to have a compressive strength of 0.28 MPa.

[0068] Example 3 A graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof. The preparation method described in this example is as follows: The graphene nanosheet suspension was ultrasonically treated to obtain a treated suspension; a magnesium source and an aluminum source were added to the treated suspension in a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.6:1.25, and first stirring was performed to obtain a mixed solution; and then the mixed solution was adjusted to a pH value of 7 with a sodium hydroxide solution to obtain a hydroxide sol.

[0069] A carbonate was added to the hydroxide sol in a molar ratio of magnesium source: carbonate of 1:0.134, and second stirring was performed to obtain a precursor sol.

[0070] The precursor sol was subjected to hydrothermal reaction to generate a precipitate; the precipitate was suction filtered, washed with water until neutral, and freeze-dried to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder.

[0071] The concentration of the graphene nanosheet suspension is 5 g / L.

[0072] The magnesium source is magnesium chloride hexahydrate; the magnesium chloride hexahydrate is of industrial purity.

[0073] The aluminum source is aluminum nitrate nonahydrate; the aluminum nitrate nonahydrate is of industrial purity.

[0074] The carbonate is anhydrous sodium carbonate; the anhydrous sodium carbonate is of industrial purity.

[0075] The temperature of the hydrothermal reaction is 120°C, and the time of the hydrothermal reaction is 6 h.

[0076] The first stirring is magnetic stirring, the time of the first stirring is 25 min, and the speed of the first stirring is 800 rpm.

[0077] The second stirring is magnetic stirring, the time of the second stirring is 20 min, and the speed of the second stirring is 500 rpm.

[0078] The time of the freeze-drying is 48 h.

[0079] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this example is 67.2°.

[0080] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in the present example was mixed with 9 parts by mass of corundum aggregate (particle size: 0.5-0.074 mm, Al2O3 content: 98 wt%), 1 part by mass of deionized water was added, and the mixture was stirred uniformly and cast, and then dried at room temperature and under normal pressure for 72 h. The corundum-based material green body prepared was detected to have a compressive strength of 0.27 MPa.

[0081] Example 4 A graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof. The preparation method described in the present example is as follows: The graphene nanosheet suspension was subjected to ultrasonic treatment to obtain a treated suspension; a magnesium source and an aluminum source were added to the treated suspension in a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.65:1.50, and first stirring was performed to obtain a mixed solution; and the mixed solution was adjusted to a pH value of 5 with a sodium hydroxide solution to obtain a hydroxide sol.

[0082] A carbonate was added to the hydroxide sol in a molar ratio of magnesium source: carbonate of 1:0.08, and second stirring was performed to obtain a precursor sol.

[0083] The precursor sol was subjected to hydrothermal reaction to generate a precipitate; the precipitate was suction-filtered, washed with water until neutral, and freeze-dried to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder.

[0084] The concentration of the graphene nanosheet suspension was 5.5 g / L.

[0085] The magnesium source was magnesium chloride hexahydrate; the magnesium chloride hexahydrate was of industrial purity.

[0086] The aluminum source was aluminum nitrate nonahydrate; the aluminum nitrate nonahydrate was of industrial purity.

[0087] The carbonate was anhydrous sodium carbonate; the anhydrous sodium carbonate was of industrial purity.

[0088] The temperature of the hydrothermal reaction was 140°C, and the time of the hydrothermal reaction was 10 h.

[0089] The first stirring was magnetic stirring, the time of the first stirring was 30 min, and the rotation speed of the first stirring was 900 rpm.

[0090] The second stirring was magnetic stirring, the time of the second stirring was 10 min, and the rotation speed of the second stirring was 550 rpm.

[0091] The time of the freeze-drying was 60 h.

[0092] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in the embodiment is 64.6°.

[0093] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in the embodiment is mixed with 9 parts by mass of corundum aggregate (particle size of 0.5-0.074 mm, Al2O3 content of 98 wt%), 1 part by mass of deionized water is added, and the mixture is stirred uniformly and cast, and the prepared corundum-based material body is dried at room temperature and under normal pressure for 72 h. The corundum-based material body is detected, and the compressive strength is 0.22 MPa.

[0094] Embodiment 5 A graphene nanosheet / magnesium-aluminum hydrotalcite composite powder and a preparation method thereof. The preparation method in the embodiment is as follows: The graphene nanosheet suspension is ultrasonically treated to obtain a treated suspension; a magnesium source and an aluminum source are added to the treated suspension in a molar ratio of magnesium source: aluminum source: graphene nanosheet of 1:0.7:1.67, and first stirring is performed to obtain a mixed solution; and the mixed solution is adjusted to a pH value of 3 with a sodium hydroxide solution to obtain a hydroxide sol.

[0095] A carbonate is added to the hydroxide sol in a molar ratio of magnesium source: carbonate of 1:0.167, and second stirring is performed to obtain a precursor sol.

[0096] The precursor sol is subjected to hydrothermal reaction to generate a precipitate; the precipitate is suction filtered, washed with water to neutral, and freeze-dried to obtain the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder.

[0097] The concentration of the graphene nanosheet suspension is 6 g / L.

[0098] The magnesium source is magnesium nitrate nine hydrate; the magnesium nitrate nine hydrate is of analytical purity.

[0099] The aluminum source is aluminum chloride six hydrate; the aluminum chloride six hydrate is of analytical purity.

[0100] The carbonate is sodium bicarbonate; the sodium bicarbonate is of analytical purity.

[0101] The temperature of the hydrothermal reaction is 150°C, and the time of the hydrothermal reaction is 12 h.

[0102] The first stirring is magnetic stirring, the time of the first stirring is 18 min, and the speed of the first stirring is 1000 rpm.

[0103] The second stirring is magnetic stirring, the time of the second stirring is 15 min, and the speed of the second stirring is 600 rpm.

[0104] The time of the freeze-drying is 72 h.

[0105] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this embodiment is 63.2°.

[0106] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this example was mixed with 9 parts by mass of corundum aggregate (particle size 0.5-0.074 mm, Al2O3 content 98 wt%), and then 1 part by mass of deionized water was added. The mixture was stirred evenly, cast into a mold, and dried at room temperature and normal pressure for 72 hours. The prepared corundum-based material body was tested to have a compressive strength of 0.24 MPa.

[0107] The beneficial effects of this specific embodiment compared with the prior art are: 1. The graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this embodiment is obtained by compounding the graphene nanosheets with the hydrophilic-rich magnesium-aluminum hydrotalcite, thereby achieving uniform coating of the graphene nanosheets with the magnesium-aluminum hydrotalcite. The prepared graphene nanosheet / magnesium-aluminum hydrotalcite composite powder is shown in the accompanying figure. Figure 1 This is a scanning electron microscope image of the graphene nanosheet / magnesium aluminum hydrotalcite composite powder prepared in Example 1; Figure 2 for Figure 1 The water contact angle diagram of graphene nanosheets / magnesium aluminum hydrotalcite composite powder is shown in FIG. Figure 1 It can be seen that the magnesium aluminum hydrotalcite is evenly coated on the surface of the graphene nanosheets. This structure significantly improves the hydrophilicity of the graphene nanosheet / magnesium aluminum hydrotalcite composite powder. Figure 2 It can be seen that the water contact angle is 64.9°, which has good hydrophilic properties, making it easy to disperse in aqueous media, effectively improving the problems of difficult dispersion and easy agglomeration of graphene nanosheet composite powders in water systems in the existing technology.

[0108] 2. The graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this specific embodiment is simultaneously composited with graphene and magnesium-aluminum hydrotalcite in a closed reactor via a one-step hydrothermal method, resulting in a simple process flow. Because the hydrothermal reaction uses water as the solvent, no additional surface modifier is required to achieve interfacial bonding between the two phases. Furthermore, no toxic byproducts are generated during the reaction process, eliminating the need for expensive equipment, complex surface modifiers, or toxic or hazardous organic solvents. The overall process is not only low-cost and environmentally friendly, but also economically beneficial and easily industrializable.

[0109] The water contact angle of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in this specific embodiment is 63.2-68.4°.

[0110] 1 part by mass of the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder prepared in the present embodiment is mixed with 9 parts by mass of corundum aggregate (particle size of 0.5-0.074 mm, Al2O3 content of 98 wt%), 1 part by mass of deionized water is added, and the mixture is stirred uniformly, cast, dried at room temperature and under normal pressure for 72 h, and the prepared corundum-based material green body is detected to have a compressive strength of 0.22-0.28 MPa.

[0111] Therefore, the present embodiment has the characteristics of simple process, low cost and environmental friendliness, and the prepared graphene nanosheet / magnesium-aluminum hydrotalcite composite powder has excellent hydrophilicity.

Claims

1. A method for preparing a graphene nanosheet / magnesium-aluminum hydrotalcite composite powder, characterized in that: The preparation method comprises the following steps: ultrasonically treating a graphene nanosheet suspension to obtain a treated suspension; adding a magnesium source and an aluminum source to the treated suspension at a molar ratio of magnesium source:aluminum source:graphene nanosheet of 1:0.5-0.7:0.67-1.67, stirring for the first time to obtain a mixed solution; and adjusting the pH value of the mixed solution to 3-11 with a sodium hydroxide solution to obtain a hydroxide sol; According to the molar ratio of the magnesium source to the carbonate of 1:0.067-0.167, carbonate is added to the hydroxide sol, and stirred for a second time to obtain a precursor sol; The precursor sol is subjected to a hydrothermal reaction to generate a precipitate; The precipitate was filtered, washed with water until neutral, and freeze-dried to obtain graphene nanosheets / magnesium aluminum hydrotalcite composite powder.

2. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The graphene nanosheet suspension is prepared by subjecting graphite to a liquid phase shear exfoliation method, and the concentration of the graphene nanosheet suspension is 4-6 g / L.

3. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The magnesium source is one of magnesium chloride hexahydrate and magnesium nitrate nonahydrate; the magnesium source is analytically pure or industrially pure.

4. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The aluminum source is one of aluminum nitrate nonahydrate and aluminum chloride hexahydrate; the aluminum source is analytically pure or industrially pure.

5. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The carbonate is one of anhydrous sodium carbonate and sodium bicarbonate; the carbonate is analytically pure or industrially pure.

6. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The temperature of the hydrothermal reaction is 110-150° C., and the time of the hydrothermal reaction is 4-12 hours.

7. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The first stirring is magnetic stirring, the first stirring time is 15-30 minutes, and the first stirring speed is 600-1000 rpm.

8. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The second stirring is magnetic stirring, the second stirring time is 10-20 min, and the second stirring speed is 400-600 rpm.

9. The method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to claim 1, wherein: The freeze-drying time is 24 to 72 hours.

10. A graphene nanosheet / magnesium aluminum hydrotalcite composite powder, characterized in that: The graphene nanosheet / magnesium-aluminum hydrotalcite composite powder is prepared by the method for preparing the graphene nanosheet / magnesium-aluminum hydrotalcite composite powder according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A silicon carbide-graphene composite powder and its preparation method

    CN107311177B

  • A large-size, high-strength graphene nanosheet / silicon carbide composite material and its preparation method

    CN108585875B

  • A silicon carbide / graphene nanosheet composite material and its preparation method

    CN109999870B

  • A method for preparing graphene nanosheet composite powder and the product

    CN115180618B